Measurement and Prediction of Residual Stresses in Low Carbon Steel Pipes Welded Shielded Metal Arc Welding - Miftin, Salah Sabbar; Mohammed, Haidar Maath; Nassar, Ameen Ahmed (Basrah Journal for Engineering Sciences, 2020)
The welding process involves a very complex thermal cycle, resulting in irreversible elastic-plastic deformation, and residual stresses in and around fusion zone and heat-affected zone (HAZ). A residual stress due to welding arises from the differential heating of the pipes due to the weld heat source. However, the presence of residual stresses in and around the weld zone reduces the strength and life of the component. The objective of this work is to measure the welding residual stress in ASTM (A-106 Gr. b) steel pipes with 4" diameter and 6 mm thickness welded manually (SMAW) in a three-pass butt joint. The shielded metal arc welding process consists of heating, melting, and solidification of parent metals and a filler material in a localized fusion zone by a transient heat source to form a joint between the parent metals. The welding process was carried out without preheating and heat treatment. This measurement of residual stress occurs by using the hole-drilling strain gauge method according to (ASTM E-873), and the experimental results for residual stresses obtained from welded carbon steel pipes are used to provide validation for finite element simulations. The welding process and welding residual stress distribution is calculated by Ansys Finite Element techniques. Theoretical considerations can be assessed by a mechanical model. Overall, there is good agreement between the predicted and measured distributions of residual stress, but the magnitude of predicted stress tends to be greater in the welding region.